The Role of PAI Teachers and the Failure of al-Qur'an Literacy in Elementary School Students - Hayi, Abdul; Alwi, Mohamad; Bilqis, Bayu Fitria (Fitrah, 2025)
The issue of Qur'anic illiteracy remains a significant educational and religious challenge in Indonesia, particularly among elementary school students. Despite the integration of Islamic Religious Education (IRE) into the national curriculum, the inability of many students to read the Qur'an properly highlights a systemic failure that demands urgent attention. This study aims to explore the pivotal role of IRE teachers in Qur'an literacy and examine the underlying causes of its persistent failure at the primary education level. Employing a library research approach with content analysis as the main method, this research synthesizes various scholarly sources and policy documents. The findings reveal that IRE teachers play a central role in shaping students' ability to read the Qur'an. However, they face multiple constraints, including limited instructional time allocated to Qur'an learning and the lack of pedagogical training in selecting developmentally appropriate methods for young learners. Moreover, the absence of structured collaboration between families, schools, and communities exacerbates the problem. The study concludes that addressing Qur'an illiteracy requires a holistic strategy that empowers teachers through professional development, extends learning time, and strengthens institutional synergy across educational and social environments.